ANTISIPASI SISWA KEMAMPUAN TINGGI DAN RENDAH DALAM MENYELESAIKAN MASALAH PERSAMAAN GARIS SINGGUNG LINGKARAN - Fatimatuz Zuhro; Palupi Medya Aslmaningsih; Ratna Kusumawati; Mohamad Yasin Fadillah (FKIP Universitas Jember, 2019)
This research is motivated by the teacher's curiosity to the extent to which students' abilities in anticipating mathematical problems. The subject consisted of MR and MT given five questions related to the tangent circle then followed by an interview. The results obtained are that MR tends to use impulsive anticipation and MT tends to use exploratory anticipation.